Has a public–private partnership resulted in action on healthier diets in England? An analysis of the Public Health Responsibility Deal food pledges. (July 2015) - Knai, C.; Petticrew, M.; Durand, M.A.; Eastmure, E.; James, L.; Mehrotra, A.; Scott, C.; Mays, N.
Highlights: We evaluated the Responsibility Deal (RD) food pledges for their effectiveness and added value. Progress reports were of poor quality overall. Most RD partners appear to have committed to interventions that probably were already underway. The RD food pledges do not reflect the most effective strategies to improve diet. Voluntary agreements need to push partners to go beyond business as usual. Abstract: The Public Health Responsibility Deal (RD) in England is a public–private partnership involving voluntary pledges between government, industry and other organisations in the areas of food, alcohol, physical activity, and health at work, and is designed to improve public health. The RD is currently being evaluated in terms of its process and likely impact on the health of the English population. This paper analyses the RD food pledges in terms of (i) the evidence of the effectiveness of the specific interventions in the pledges and (ii) the likelihood that the pledges have brought about actions among organisations that would not otherwise have taken place. We systematically reviewed evidence of the effectiveness of the interventions proposed in six food pledges of the RD, namely nutrition labelling (including out-of-home calorie labelling and front-of-pack nutrition labelling), salt reduction, calorie reduction, fruit and vegetable consumption, and reduction of saturated fats. We then analysed publically available data on organisations' plans and progress towards achieving the pledges, and assessed the extent to which activities among organisations could be brought about by the RD. Based on seventeen evidence reviews, some of the RD food interventions could be effective, if fully implemented. However the most effective strategies to improve diet, such as food pricing strategies, restrictions on marketing, and reducing sugar intake, are not reflected in the RD food pledges. Moreover it was difficult to establish the quality and extent of implementation of RD pledge interventions due to the paucity and heterogeneity of organisations' progress reports. Finally, most interventions reported by organisations seemed either clearly (37%) or possibly (37%) already underway, regardless of the RD. Irrespective of the nature of a public health policy to improve nutritional health, pledges or proposed actions need to be evidence-based, well-defined, and measurable, pushing actors to go beyond 'business as usual' and setting out clear penalties for not demonstrating progress.